(untitled) (Tanzania Medical Journal, 2016)
IntroductionAvailability of HAART has improved the outcome of HIV-associated neurocognitive disorders (HAND) though the prevalence is still high. Routine screening for HAND may offer room for early detection and prompt management that may improve overall outcome.ObjectiveTo compare the performance of International HIV dementia scale (IHDS) and Mini Mental Status Examination (MMSE) Scale in assessing HIV-associated neurocognitive disorders.MethodsThis was a case- control study involving 351 HIV-cases and 150 HIV-negative controls. International HIV dementia scale and Mini Mental Status Examination scale were used to screen for neurocognitive deficits.ResultsFor cases, 91(25.9%) were males and 260(74.1%) were females while for 150 controls, 38(25.3%) were males and 112 (74.7%) were females. Under IHDS score 240(68.4%) of cases had HAND compared to 10(2.8%) when MMSE was used. The mean scores under MMSE for cases was 29±1.7 compared to 29.3± 1.2 for controls (p = 1.00). The mean IHDS scores for cases was 9.35 ± 1.89 compared to 10.35±0.89 (p < 0.0001) for controls.ConclusionOur findings suggests that IHDS has better sensitivity in detecting cases of HAND and perform better in identifying HIV/AIDS cases that requires further cognitive evaluation on comprehensive neuropsychological batteries.